Reluctant Partners : Implementing Federal Policy. - Stoker, Robert P. (Pittsburgh : University of Pittsburgh Press, 1992)
Constitutional principles divide authority between market and state and within the structure of the state itself. This diffusion of authority is valuable because it defends against the excesses of national government, causing federal policy initiatives to be more attuned to local jurisdictions, and creating a context in which free enterprise may flourish. However, this diffusion of authority weakens the control that federal officials enjoy over resources vital.
Intro -- Contents -- List of Figures -- List of Tables -- Preface -- 1. The Implementation Paradox -- 2. Authority, Exchange, and Governance -- 3. Implementation Regimes -- 4. The Politics of Implementation Regimes -- 5. Policy Reform and Implementation Preformance -- 6. Not in My Backyard -- 7. Meeting the Callenge -- Notes -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Federal government -- United States; Authority; Capitalism -- United States; United States -- Economic policy -- 1945-1960 -- Decision making; Autorité.; États-Unis -- Politique économique -- 1945-1960 -- Prise de décision.; POLITICAL SCIENCE / General